"From doing to knowing": medical students' experiences of working as Healthcare Assistants. Issue 4 (4th July 2022) - Davison, Elizabeth; Semlyen, Joanna; Lindqvist, Susanne
ABSTRACT: There is growing recognition that doctors need to deliver person-centered care. More evidence is needed on how to best equip students in an already busy curriculum. Providing medical students with the opportunity to work as Healthcare Assistants (HCAs) can help them develop the desired skills. This study examined medical students' experiences of working as HCAs and perceived impact on their future practice. Adopting an Interpretative Phenomenological Analysis approach, we analyzed narratives from two focus groups of 13 'Year 0ʹ and 'Year 1ʹ medical students, who had completed an HCA project. This project allowed participants to experience a new dimension of patient care whereby learning by "doing" evolved to a deeper level of "knowing" patients, the HCA role and the wider team. Four major themes were identified: seeing the doctor: gaining new perspectives; building confidence: learning from and about patients; understanding the overall patient experience: providing personal care; finding "the person behind the patient": exploring beyond the diagnosis. This study suggests that working as an HCA enables participants to develop sustainable skills that equip them for their future role as doctors able to deliver person-centered care as part of an interprofessional team. Recommendations for inclusion of this type of intervention into the medical curriculum are discussed.